Mutations in KCNJ11, which encodes Kir6.2, are a common cause of diabetes diagnosed in the first 6 months of life, with the phenotype determined by genotype. - Flanagan, SE; Edghill, E; Gloyn, A; Ellard, S; Hattersley, A (2006)
AIMS/HYPOTHESIS: Heterozygous activating mutations in KCNJ11, which encodes the Kir6.2 subunit of the pancreatic ATP-sensitive potassium (K(ATP)) channel, cause both permanent and transient neonatal diabetes. A minority of patients also have neurological features. The identification of a KCNJ11 mutation has important therapeutic implications, as many patients can replace insulin injections with sulfonylurea tablets. We aimed to determine the age of presentation of patients with KCNJ11 mutations and to examine if there was a relationship between genotype and phenotype. SUBJECTS AND METHODS: KCNJ11 was sequenced in 239 unrelated patients from 21 countries, who were diagnosed with permanent diabetes before 2 years of age. RESULTS: Thirty-one of the 120 patients (26%) diagnosed in the first 26 weeks of life had a KCNJ11 mutation; no mutations were found in the 119 cases (0%) diagnosed after this age. Fourteen different heterozygous mutations were identified, with the majority resulting from de novo mutations. These include seven novel mutations: H46Y, R50Q, G53D C166Y, K170T, L164P and Y330S. All 11 probands with the most common mutation, R201H, had isolated diabetes. In contrast, developmental delay in addition to diabetes was seen in four of five probands with the V59M mutation and two of four with the R201C mutation. Five patients with developmental delay, epilepsy and neonatal diabetes (DEND) syndrome had unique mutations not associated with other phenotypes. CONCLUSIONS/INTERPRETATION: KCNJ11 mutations are a common cause of permanent diabetes diagnosed in the first 6 months and all patients diagnosed in this age group should be tested. There is a strong genotype-phenotype relationship with the mutation being an important determinant of associated neurological features.